Surveilans Tuberkulosis di Jawa Timur - Tasalina Yohana Parameswari Gustam (Universitas Pahlawan Tuanku Tambusai, 2023)
Surveillance is the act of observing a problem continuously starting from data collection, data analysis or processing, data interpretation, and dissemination of data used for planning, implementation, and evaluation of health management programs. TB is still a global problem with high mortality and morbidity worldwide. Indonesia is ranked second as the country with the highest number of TB cases. East Java Province has the second highest TB burden after West Java. The largest population in East Java is Surabaya City with 2,801,409 people. Methods: This is a descriptive observational study, that focuses on the Tuberculosis disease surveillance program in the East Java Provincial Health Office, located at Jalan Ahmad Yani No. 118 Surabaya. Results: Analysis of tuberculosis surveillance data from the Public Health Office of East Java in 2014 varies between 5.43% and 78.15%, with a Case Notification Rate (CNR) is 110. Analysis of tuberculosis surveillance data from the Public Health Office of East Java in 2015 the prevalence of TB in the district ranged between 5.73% and 55.1%, with the number Case Notification Rate is 111. Surveillance of tuberculosis in East Java Health Office using the procedure outlined in national guidelines tuberculosis disease control. This analysis revealed that the Case Detection Rate in East Java at 2015 was 55,1%, and it is lower compared to the national target achievement in CDR which is 70%, also for the target of case notification rate. Conclusion: The tuberculosis CDR in East Java at 2015 is still lower than the national target in tuberculosis CDR and it shows that more effort is needed to increase activities on case notification and to stop the transmission of TB by strengthening the component from TB strategy. Keywords: Surveillance, Tuberculosis, East Java Indonesia, Epidemiology